Associations of genotype variants of single nucleotide polymorphism of gene orosomucoid-1-like-protein 3 and atopic diseases at children. - Dytiatkovsky, V. O.; Abaturov, O. E.; Naumenko, N. V.; Pinayeva, N. L.; Alifirenko, O. O. (Medicni Perspektivi, 2019)
The paper presents data of the firstly conducted in Ukraine own study of associations of the single nucleotide polymorphism (SNP) rs7216389 of orsomucoid-1-like protein 3 gene (ORMDL3) variants’ with atopic diseases in children. Aim: to detect clinical significance of the SNP rs7216389 ORMDL3 in genesis of atopic diseases in children. We examined 153 children aged 3 to 18 years. The main group consisted of 119 children with clinical manifestations of atopic diseases with elevated total serum immunoglobulin E, confirmed by immunofluorescence assay method. The comparison group consisted of 34 children with a non-aggravated individual or family allergic anamnesis in whom there was detected the absence of any clinical syndromes and symptoms of atopic diseases and, mostly, physiological parameters of the serum total immunoglobulin E by immunofluorescence assay method. All the children were genotyped by ORMDL3 gene using polymerase chain reaction in real time with a restricted fragment length polymorphism. The genotype T/T within SNP rs7216389 of ORMDL3 gene significantly prevails among the children with atopic diseases and is associated with an increased incidence risk of seasonal allergic rhinoconjunctivitis (SARC) by 4.11 times (95% CI 1.55; 16.61), perennial allergic rhinitis (PAR) by 5.07 times (95% CI 1.22; 13.90) times and bronchial asthma (BA) by 10.31 times (95% CI 2.50; 42.62). Children with genotype T/T in locus rs7216389 of the ORMDL3 gene are the increased risk group for developing the atopic diseases. Children with genotype C/C in locus rs7216389 of the ORMDL3 gene are the decreased risk group for the development of atopic dermatitis.